Pengaruh Konsep Fasilitas Ruang Tunggu Keberangkatan Terhadap Minat Pengguna Jasa Layanan Di Bandar Udara Internasional Banyuwangi - Afifah Farah Fauziyyah; Maria Valeria Roellyanti (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
Each airport definitely has its own concept or characteristics, as is the case with Banyuwangi airport which has an architectural concept, namely the green airport concept which has a facility concept that is different from others, especially in the buildings at the airport terminal. This research was conducted with the aim of finding out whether there is an influence of the concept of departure waiting room facilities on the interest of service users at Banyuwangi International Airport. Apart from that, it also aims to find out how much influence the concept of departure waiting room facilities has on the interest of service users at Banyuwangi International Airport. In this research there is one independent variable, namely the concept of waiting room facilities (X) and the dependent variable, namely service user interest (Y). This research is quantitative research because the main focus of this research is to find out how much influence the independent variable (X) has on the dependent variable (Y) that will be studied. The population includes passengers in the Banyuwangi airport departure waiting room and a sample of 30 respondents. Data collection techniques use questionnaires, observation, documentation and literature study. The measurement scale uses a Likert scale. The data analysis technique uses simple regression analysis which is processed using SPSS (Statistical Product and Service Solutions) For Windows release 22.0. The research results prove that there is a significant influence between the concept of departure waiting room facilities on the interest of service users at Banyuwangi International Airport. The t test results prove that it is 0.000 < 0.05, which means the significant value is smaller than 0.05. The results of the coefficient of determination R2 of 0.317 can be concluded that the concept of departure waiting room facilities influences service user interest by 31.7% while the remaining 68.3% is influenced by other variables not discussed in this research.